Fractais de Rauzy, autômatos e frações contínuas - Pavani, Gustavo Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this doctoral thesis is to study some topological and arithmetical properties of a class of Rauzy fractals which do not have the (F) Property. In particular we proved that the Rauzy fractals of this class induce a periodic tiling of the complex plane. Furthermore, we studied the construction of a nite automaton able to generate the boundary of these fractals, and to parametrize them. This automaton is also used to establish conditions on the number of neighboors of these fractals. We also studied the best simultaneous diophantine approximation for pairs of algebraic numbers v = ( ; 2), where 1= is a cubic Pisot number whose conjugates are not real numbers, and 1= does not satisfy the (F) Property

O objetivo desta tese e estudar algumas propriedades topol ogicas e aritm eticas de uma classe de fractais de Rauzy que não possui a Propriedade (F). Em particular provamos que os fractais de Rauzy desta classe induzem um azulejamento peri odico do plano complexo. Al em disso, constru mos um automático nito capaz de gerar a fronteira desses fractais e parametriz a-las. Este autômato tamb em e utilizado para estabelecer condiçõees sobre o n umero de vizinhos que compõem as fronteiras desses fractais. Estudamos tamb em as melhores aproximações diofantinas simultâneas para pares de n umeros alg ebricos v = ( ; 2), em que 1= e um n umero de Pisot c ubico cujos conjugados não são n umeros reais e 1= não satisfaz a Propriedade (F)
Keywords: Matemática; Teoria de sistemas dinâmicos; Fractais; Topologia